POTENTIALITIES OF MEMORY CAFéS IN SUPPORTING PEOPLE WITH DEMENTIA AND THEIR CARERS - Arajo, L. (Innov Aging, 2017)
Alzheimer/Memory Cafés recently emerged in several European countries and in North America as an initiative that involves people with dementia, their family/friend carers, and all others interested in dementia, focused in socialization with an educational component. The sessions occur monthly and include a presentation on a different topic alternately with a stimulation/recreation activity, as well as refreshments, in a very informal and café-like atmosphere. The present study gathers evidence from eleven Cafés groups developed across Portugal in order to present the impact of this type of intervention in supporting people with dementia and their family members/carers. During the last three years of program implementation, 177 persons with dementia and 737 family members/carers, as well as 142 persons with memory problems and 272 persons interested on this topic have participated on the 226 Cafés sessions that were developed. Qualitative data was collected with a subgroup of family members (N= 50) regarding their opinion on the main benefits of attending sessions to themselves and their relatives with dementia. Main key themes from the analysis, such as dementia-friendly environments, where family can be together with their relatives, other caregivers and persons with dementia socializing in the community, and the potential of Cafés for reducing the stigma, obtaining information and discussing the disease openly with other persons (e.g., family, carers, professionals, volunteers) are presented and discussed as important potentialities of this type of support available to people with dementia and their carers.